The Black International. L - Lamberts, Emiel (ed.) (KADOC-Studies, 2002)
This book outlines the history of the Black International, a secret organisation, directly linked to the Vatican, which brought together the leaders of the Catholic committees in nine European countries. The organisation tried to stem the tide of liberalism, socialism and nationalism that threatened the Catholic Church at the end of the 19th century. The story of the origins, workings and ending of this International at times seems like a detective story. The book offers an extensive discussion of the influence of this organisation on the press policy and the international position of the Vatican. It also explores its impact on the development of militant Catholicism and, through its after-effects in the Union of Fribourg (1884-1891) on the emergence of social Catholicism in Europe. L'Internationale noire